2000
DOI: 10.1128/iai.68.2.577-583.2000
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils Play a Protective Nonphagocytic Role in SystemicMycobacterium tuberculosisInfection of Mice

Abstract: Evidence showing that neutrophils play a protective role in the host response to infection by different intracellular parasites has been published in the past few years. We assessed this issue with regard to the infection of mice with Mycobacterium tuberculosis. We found a chronic recruitment of neutrophils to the infection foci, namely, to the peritoneal cavity after intraperitoneal infection and to the spleen and liver after intravenous inoculation of the mycobacteria. However, bacilli were never found assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
215
3
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 256 publications
(239 citation statements)
references
References 47 publications
14
215
3
2
Order By: Relevance
“…Thus, C. albicans strains that induce healing infection are capable of stimulating neutrophil IL-12 production, and this is required to control infection (3,19,29). Recent data also suggest that control of murine Mycobacterium tuberculosis infection is dependent upon an immunoregulatory function of neutrophils (30). Here, we show that depriving mice of their neutrophils at the time of infection results in decreased systemic levels of IL-12 p40 (Fig.…”
Section: Discussionmentioning
confidence: 56%
“…Thus, C. albicans strains that induce healing infection are capable of stimulating neutrophil IL-12 production, and this is required to control infection (3,19,29). Recent data also suggest that control of murine Mycobacterium tuberculosis infection is dependent upon an immunoregulatory function of neutrophils (30). Here, we show that depriving mice of their neutrophils at the time of infection results in decreased systemic levels of IL-12 p40 (Fig.…”
Section: Discussionmentioning
confidence: 56%
“…Neutrophil depletion during early mycobacterial infection exacerbates disease and dysregulates granuloma formation (23)(24)(25)(26). However neutrophils are associated with tissue damage and necrosis in late disease and are a feature of granulomas in gene-deletion models associated with increased susceptibility to tuberculosis (27)(28)(29)(30)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…64 Another study demonstrated significant reduction in the expression of both receptors on neutrophils in persons with pulmonary TB and/or HIV infection. 65 Since neutrophils are known to play a protective nonphagocytic role in the initial host defense mechanisms against M. tuberculosis, 66,67 reduced expression of these receptors could impair the chemotactic response of neutrophils to IL-8 and hence the immune response in mycobacterial infection. These findings also highlight the importance of these receptors in neutrophil functions.…”
Section: Decay Of Ldmentioning
confidence: 99%